AI Investments Allow Emerging Markets to Develop and Expand Sophisticated Manufacturing Capabilities - Manchanda, Sumit (International Finance Corporation, Washington, DC, 2020)
As advances in machine learning, computer vision, and robotics help manufacturers around the world improve their processes and produce new and more complex products, artificial intelligence (AI) is becoming an integral tool of modern manufacturing, and one that is increasingly important to the industry’s future. By combining large volumes of data with the computing power to simulate human thinking, AI is increasing the efficiency, capacity, and complexity of factory floors, and is introducing robotics, the Internet of Things, and other cutting-edge innovations to manufacturing value chains across the globe. Artificial intelligence is a critical enabler of manufacturing complexity that is essential for companies to produce an expansive range of sophisticated products and dynamically engage with regional and global value chains. Firms and economies can increase both their manufacturing complexity and their market competitiveness by developing the foundational capabilities and know-how needed to adopt AI and other advanced technologies.